PENINGKATAN KEMAMPUAN PENGELOLA UKM SEPATU DALAM MENGGUNAKAN TEKNOLOGI DAN INFORMASI DI DESA SAMBIROTO-SOOKO-KABUPATEN MOJOKERTO - Sugeng Mulyono; Jamal Abdul Nasir (Institute of Research and Community Outreach - Petra Christian University, 2014)
The purpose of this community service is to optimize the performance of SMEs managers of shoes financial governance, marketing and the ability to utilize technology and marketing information. Method of execution by combining classical training, mentoring and computer support to stimulate shoe business managers to implement training materials. Training and mentoring successfully improving the management capabilities of SMEs of shoes, although still not optimal, in the financial governance, marketing methods and website utilization for marketing.